The developmental and performance trends in Olympic track and field - Tilinger, P.; Kovac, K. (2000)
In our research, we were concerned with the creation of suitable evaluation systems and predictions of developmental trends in sport. Olympic Track and Field events were analyzed from 1972 to 1996 in the following areas: performance trends, relationship between politics and sport, development of organizational structures, rules development, trends in sport training, development of technique, development of equipment and material support for Track and Field. The research methods included statistical analysis of performances at Olympic games, analysis of literature, interviews and questionnaires administered to athletes and coaches, who have participated at the European and World Championships and the Olympic games. Total of 150 athletes and 130 coaches from the Czech Republic and other parts of Europe participated in our study. The prediction system of the developmental trends in Track and Field for the next 20 years was based on the synthesis of information from the analysis of previously investigated areas. The results of our study suggest that sport will continue to play a very important role in publicity and promotion of overall development of many countries. The performance levels will continue to grow because of the development of new knowledge, which contributes to a higher quality of practice, improvement of technique, and above all, because of improved material support for athletics. The coaches and athletes believe that the trend toward increase frequency of competition among the top world athletes will continue because of its attractiveness for sponsors and media. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)